Hi Sharon,
In the inductive step I assumed that the expression is true for n = k, that is
2 + 7 + 12 + ...+ (5k  3) = k(5k  1)/2
I then want to use this assumption and prove the expression is valid when n = k + 1, which is
2 + 7 + 12 + ...+ (5k  3) + (5(k+1)  3) = (k+1)(5(k+1)  1)/2.
The right side simplifies to (k + 1)(5k + 4)/2
Using the assumption that the expression is valid for n = k the left side becomes
2 + 7 + 12 + ...+ (5k  3) + (5(k+1)  3)
= k(5k  1)/2 + (5(k+1)  3)
Show that this simplifies to (k + 1)(5k + 4)/2
Penny
